Lung cancer and risk of cardiovascular mortality - Wang, Chengshi; Wang, Zhu; Yang, Jing; Zhang, Songbo; Zhang, Purong; Yang, Ye (Frontiers in Cardiovascular Medicine, 2025)
PurposeThe aim of the present study was to investigate the cardiovascular mortality risk among lung cancer patients compared to the general population.MethodsUsing data from the National Cancer Institute's Surveillance, Epidemiology, and End Results program, we conducted a population-based cohort study including 278,418 lung cancer patients aged over 30 years between 1 January 1990 and 31 December 2020 as well as the general population. Poisson regression was employed to calculate incidence rate ratios (IRRs) for cardiovascular mortality.ResultsPatients exhibited a significantly higher IRR of cardiovascular mortality risk compared to the general population [IRR 1.74, 95% confidence interval (CI) 1.71–1.77]. The risk was most pronounced in patients aged 30–79 years (IRR 2.61, 95% CI 2.55–2.66), peaking at ages 30–34 years (IRR 48.93, 95% CI 21.98–108.92). Elevated cardiovascular mortality risks were observed across all subgroups, including diseases of the heart (IRR 1.79, 95% CI 1.75–1.82), cerebrovascular diseases (IRR 1.52, 95% CI 1.45–1.59), and other cardiovascular diseases (IRR 1.78, 95% CI 1.67–1.90). The first month after diagnosis presented the highest risk for patients aged 30–79 years (IRR 12.08, 95% CI 11.49–12.70) and ≥80 years (IRR 4.03, 95% CI 3.70–4.39). Clinical characteristics significantly modified cardiovascular mortality.ConclusionsIntegrating cardiovascular disease monitoring and proactive management into lung cancer treatment protocols is essential to the improvement of overall survival and quality of life for lung cancer patients, particularly those who were young or with advanced tumor stage.